2020
DOI: 10.7150/ijms.49030
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between metabolic syndrome and bone mineral density among Malaysians

Abstract: Objectives: Metabolic syndrome (MetS) is a cluster of metabolic abnormalities that elevates the individual risk of cardiovascular diseases. These abnormalities are also known to alter bone remodelling. Therefore, MetS may be associated with osteoporosis. This study aims to determine the association between MetS and its components and bone mineral density (BMD) assessed by dual-energy X-ray absorptiometry (DXA) among Malaysians. Methods: 400 Malaysians aged ≥ 40 years (52.5% women) residing in Klang Valley, Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 59 publications
2
18
0
1
Order By: Relevance
“…Patients undergoing chronic dialysis have a lower BMD than healthy subjects of similar age due to CKD-related mineral and bone disorders [ 45 ]. Abdominal obesity can reflect higher mechanical loading on the bone, which then stimulates bone accrual [ 12 ]. Many studies have reported a positive relationship between TG level and BMD [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing chronic dialysis have a lower BMD than healthy subjects of similar age due to CKD-related mineral and bone disorders [ 45 ]. Abdominal obesity can reflect higher mechanical loading on the bone, which then stimulates bone accrual [ 12 ]. Many studies have reported a positive relationship between TG level and BMD [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported inconsistent and controversial relationships between components of MetS and osteoporosis [ 11 ]. With regard to the components of MetS, abdominal obesity has been shown to increase the mechanical load on the body and stimulate bone accrual [ 12 ]. Hypertension-induced abnormal calcium metabolism and interactions between bone marrow and hypertension have been reported [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GM may contribute to metabolic health, but dysbiosis in GM composition triggers metabolic syndrome. Metabolic syndrome is a combination of abnormalities contributing to different diseases such as malnutrition, non-alcoholic liver disease, obesity, cardio-metabolic diseases and type-2 diabetes [4,62,63]. Deficiency of SIRT3, known as a mitochondrial deacetylase, is a significant cause of metabolic syndrome.…”
Section: Metabolic Impairment and Admentioning
confidence: 99%
“…The subjects were classified as having WC obesity (≥80 cm), BMI obesity (>25 kg/m 2 ) or both. NCEP-ATPIII Compared to non-obese subjects, the risk of osteoporosis: Reduced in BMI-defined obesity: OR 0.42, 95% CI 0.18~0.99 Reduced in BMI or WC-defined obesity: OR 0.66, 95% CI 0.44~1.00 Chin et al (2020) 16 Cross-sectional study 400 Malaysians aged ≥ 40 years (52.5% women) in Klang Valley Joint interim statement Before BMI-adjustment Lumbar spine: β 0.128, 95% CI 0.022~0.035 Femoral hip: β 0.165, 95% CI: 0.081~0.249 Osteoporosis risk: OR 0.545, 95% CI 0.221–1.346 After BMI-adjustment Lumbar spine: β 0.009, 95% CI −0.097~0.115 Femoral hip: β 0.006, 95% CI −0.079~0.091 Osteoporosis risk: OR 0.907, 95% CI 0.186~4.411 Notes: All the studies performed the BMD measurement via dual-energy X-ray absorptiometry, except for 42 44 (labeled with $ ), which used quantitative ultrasonometry. Abbreviations: β, standard regression coefficient; AHA/NHLBI, American Heart Association/National Heart, Lung, and Blood Institute; BMD, bone mineral density; BMI, body mass index; BUA, broadband ultrasound attenuation; CI, confidence interval; DBP, diastolic blood pressure; FBG, fasting blood glucose; HDL-c, high-density lipoprotein cholesterol; HOMA-IR, homeostatic model assessment of insulin resistance; HPT, hypertension; IDF, International Diabetes Federation; LDL-c, low-density lipoprotein cholesterol; MetS, metabolic syndrome; NAFLD, non-alcoholic fatty liver disease; NCEP-ATP–III, National Cholesterol Education Program Adult Treatment Panel III; NS, not significant; OR, odds ratio; QUI, quantitative ultrasound index; SBP, systolic blood pressure; SD, standard deviation; SEM, standard error of mean; SOS, speed of sound; TG, triglyceride; WC, waist circumference; WMD, weighted mean difference.…”
Section: Relationship Between Mets and Bone Geometrymentioning
confidence: 99%
“…15 Multiple cross-sectional studies reported a positive relationship between MetS and BMD. [16][17][18][19] The Third National Health and Nutrition Examination Survey (NHANES III) (n=8197, ≥20 years) reported a higher femoral neck BMD among subjects with MetS compared to subjects without MetS. Adjustment for BMI attenuated the difference in BMD between the two groups.…”
Section: Relationship Between Mets and Bone Mineral Density Positive mentioning
confidence: 99%